Islamic Humanity as an Indicative of Islamic Rationality - Hassan Sobhani; Ata'ollah Rafiei Atani (حکمت اسرا, 2012)
In this article we try to separate the concept of “practical rationality” from “cognitive or scientific rationality” to illustrate that this is the cognitive rationality which is connected to the “agent of cognition” and the “humanity's realm” taking its validity from the validity of rationality in paradigms of the philosophy of science. But on the other hand the practical rationality, which is connected to the “cognition” of the humanities, takes its validity from philosophy and ethical system. Furthermore the mission of cognitive rationality in the humanity's realm is the systematic identification of human's behavior and actions, because humans act in a way that they consider ethically true. Hypotheses in the humanities, which are a primary concept on identifying of human's behavior and actions, have the ethical quiddity, because they are indicatives of the system of humans' action rationality. But it is possible to prove the hypotheses by scientific reality-indicative methods. The conventional humanities generally include some hypotheses trying to introduce the practical rationality system of the western communities. Even if that is the case and they have had a system of practical rationality, this means that they are only committed to their own moral code. In this article it will be shown that the “Islamic practical rationality” is a “fuzzy rationality” being able to explain all the human being's behavior. For this reason, the Islamic humanities are more universal than conventional humanities. It should be noted that in this article the Islam's attitude toward rationality and humanities is cognitive approach not sociological and cultural one.